Role of hydrogen peroxide and Pharmaplant-turbo against cucumber powdery mildew fungus under organic and inorganic production - Hafez, Y. M.; Bayoumi, Y. A.; Pap, Z.; Kappel, N. (International Journal of Horticultural Science, 2008)
Cucumber leaves have been sprayed with a solution of hydrogen peroxide (H202) or Pharmaplant-turbo combined with organic or inorganic fertilizers under plasic house. Under the influence of H202, leaves exhibited resistant against Podoshaera fusca fungus, the causal agent of cucumber powdery mildew. H202 (15 mM) was able to decrease the disease severity from 90.4% to 12% in two experiments conducted in two seasons. Pharmaplant-turbo (Turbo) is new chemical compound and used as an antifungal compound. Turbo in 1 ml/L was able to decrease the disease severity from 90.4% to 11.5% in the both experiments as well. Both of H202 and Turbo were combined with organic treatment (compost + compost tea + seaweed extracts) which showed significant effect against cucumber powdery mildew fungus and strongly suppressed it as compared to control leaves. Organic treatment produced higher vegetative growth characters and greater early and total yields as compared to inorganic treatment, also organic fruits produced the lower nitrate content and the higher ascorbic acid content as compared to inorganic fruits. Our study have indicated that, H202 and Turbo combined with organic fertilizers play a role in the resistance of cucumber against powdery mildew by decreasing the disease severity. We suggest to give more attention to the direct application of H202 in low concentration and Turbo against powdery mildew diseases and other plant diseases.